Implementation of Character Education-Based Cooperative Learning Management at SD Negeri 380 Salupao - Agus Rante Rapa; Muhaemin Muhaemin; Kartini Kartini (International Journal of Educational Administration, Management, and Leadership, 2024)
This study aims to describe how character education-based cooperative learning management is implemented at SD Negeri 380 Salupao, identify its strengths and weaknesses, and develop strategies to improve the effectiveness of character education in the elementary school setting. The research used a descriptive qualitative approach, collecting data through observations, in-depth interviews, and documentation. The findings show that the implementation of cooperative learning management at SD Negeri 380 Salupao involves integrating character values such as cooperation, responsibility, and tolerance into each group learning activity. The strengths include students’ active participation, which helps build positive character traits. However, the weaknesses involve limited teacher training in creating consistent cooperative learning strategies grounded in character values. Suggested improvements include enhancing teacher skills through ongoing training, fostering better collaboration between teachers and parents, and developing more systematic and contextually relevant learning tools. These findings highlight the importance of a learning management approach that not only emphasizes academic success but also develops students’ character through a cooperative method grounded in core values.